2018
DOI: 10.1021/jacs.8b06836
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for O–O Bond Formation via Radical Coupling of Metal and Ligand Based Radicals: A New Pathway

Abstract: Artificial photosynthesis carries promise to deliver abundant clean energy for the needs of a growing population. Deep mechanistic understanding is required to achieve rational design of fast and durable water oxidation catalysts. Here we provided first evidence for a new mechanism of the OO bond formation via radical coupling of the oxidized metaloxo of radicaloid character (Ru IV O) and ligand based radical ([ligand-NO] +• cation radical). OO bond formation is facilitated via spin alignment and takes pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 51 publications
1
47
1
Order By: Relevance
“…Since the first discovery by Meyer and coworkers that an oxo-bridged dinuclear ruthenium(III) complex Ru III -O-Ru III (Gersten et al, 1982), known as ''blue dimer,'' was active for water oxidation, a large number of molecular catalysts have been identified and considerable knowledge with respect to their activity has been generated (Kä rkä s et al, 2014;Blakemore et al, 2015;Zong and Thummel, 2005;Concepcion et al, 2008;Shigeyuki and Ken, 2009;Duan et al, 2009). A survey of these molecular catalysts reported to date revealed that Ru-bda (bda = 2,2 0 -bipyridine-6,6 0 -dicarboxylic acid) complex is the most efficient water oxidation catalyst (Duan et al, 2009, which had been demonstrated to operate O-O bond formation via coupling two oxo-radical (I2M) pathway, rather than via water nucleophilic attack (WNA) pathway (Zhan et al, 2017;Hessels et al, 2017;Xie et al, 2018;Pushkar et al, 2018). From a mononuclear Ru(bda) (pic) 2 (pic = 4-picoline), Sun and Sakai independently reported an oxido-bridged trinuclear species Ru III -O-Ru IV -O-Ru III Tsubonouchi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Since the first discovery by Meyer and coworkers that an oxo-bridged dinuclear ruthenium(III) complex Ru III -O-Ru III (Gersten et al, 1982), known as ''blue dimer,'' was active for water oxidation, a large number of molecular catalysts have been identified and considerable knowledge with respect to their activity has been generated (Kä rkä s et al, 2014;Blakemore et al, 2015;Zong and Thummel, 2005;Concepcion et al, 2008;Shigeyuki and Ken, 2009;Duan et al, 2009). A survey of these molecular catalysts reported to date revealed that Ru-bda (bda = 2,2 0 -bipyridine-6,6 0 -dicarboxylic acid) complex is the most efficient water oxidation catalyst (Duan et al, 2009, which had been demonstrated to operate O-O bond formation via coupling two oxo-radical (I2M) pathway, rather than via water nucleophilic attack (WNA) pathway (Zhan et al, 2017;Hessels et al, 2017;Xie et al, 2018;Pushkar et al, 2018). From a mononuclear Ru(bda) (pic) 2 (pic = 4-picoline), Sun and Sakai independently reported an oxido-bridged trinuclear species Ru III -O-Ru IV -O-Ru III Tsubonouchi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our estimate for the gas-phase model shows a quantitatively different free energy profile with the barrier for the forward reaction significantly lower (19 kcal mol −1 ), and a higher stability of the product state as shown in Figure 2b (∆G = 12.5 kcal mol −1 ). Pushkar and co-workers report a value for ∆G for the catalyst activation step in gas-phase (17.3 kcal mol −1 ), using a hybrid (B3LYP) functional with an implicit solvent model (CPCM) for water [19]. Representative snapshots of the initial, transition and product states during the catalyst activation pathway are shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…Naturally, a favorable interaction between the axial/equatorial ligands can help reduce the overall steric hindrance, thereby facilitating interaction of the ruthenium-oxos with minimal reorganization [14,15]. In a recent work, Pushkar and co-workers reported a mononuclear Ru based complex [Ru I I (bpy) 2 (bpy-NO)] 2+ (A) that is proposed to operate via a metal-ligand radical coupling pathway (MLC) during the O-O bond formation step [19]. This involves an intramolecular coupling between the metal and ligand generated radicals (Figure 1c), thereby eliminating the need for the dimerization of the oxo species in the right orientation and overcoming steric and solvation barriers, that is the main limitation of the I2M based complexes.…”
Section: Introductionmentioning
confidence: 99%
“…formation was proposed for some water oxidation catalysts. 40,41 Currently, experimental con rmation of the direct carboxylate ligand involvement in O-O bond formation is lacking. Nevertheless, for complete analysis of all possible pathways, S [Co III 3 O 4 Co III (OOC(O)CH 3 ) bridging ] 0 product of O-O bond formation was computed (Table 1).…”
Section: Direct Involvement Of Oxygen-containing Ligands Such As N-oxmentioning
confidence: 99%